2021
DOI: 10.1002/pa.2685
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health services and the elderly: Assessing the determinants of technology adoption readiness in Pakistan

Abstract: Technological innovations changed people's daily lives. Wireless technologies, such as mobile phones and other portable gadgets, are becoming an essential part of each generation. With the increasing size of the elderly population around the world, opportunities for the older generation to use wireless technologies, such as gerontechnologies, are increasing. Older adults can use mobile health (mHealth) to receive healthcare at their doorstep. This study uses the UTAUT theoretical framework, extended to perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…The study also indicated that women showed more anxiety disorders than men in the utilization of mobile health apps ( 28 ). In assessing the mobile health services for the elderly in Pakistan, it was demonstrated that performance expectancy, effort expectancy, social influence, facilitating conditions, perceived ubiquity, and perceived trust drive m-health behavioral adoption ( 29 ). A similar study conducted in China showed that performance expectancy, effort expectancy, and facilitating conditions influence the readiness of citizens to use mobile health systems ( 30 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also indicated that women showed more anxiety disorders than men in the utilization of mobile health apps ( 28 ). In assessing the mobile health services for the elderly in Pakistan, it was demonstrated that performance expectancy, effort expectancy, social influence, facilitating conditions, perceived ubiquity, and perceived trust drive m-health behavioral adoption ( 29 ). A similar study conducted in China showed that performance expectancy, effort expectancy, and facilitating conditions influence the readiness of citizens to use mobile health systems ( 30 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pakistan's diverse cultural landscape influences how individuals perceive and respond to technology, making it essential to explore how cultural nuances impact the effects of technology on outcomes like consumer behaviour, job performance, and education. This research can inform tailored interventions and policies, addressing the specific concerns of Pakistani individuals while optimising strategies for technology adoption, particularly amongst groups prone to anxiety or with limited digital literacy (Khan et al, 2022). Additionally, findings can enhance digital literacy programs, help businesses design marketing strategies that resonate with the target audience's anxieties and preferences, and address cybersecurity and privacy concerns in an increasingly digital Pakistan (Naveed and Ameen, 2017).…”
Section: The Moderating Role Of Technology Anxietymentioning
confidence: 93%
“…The contributions within this topic collectively underscore the critical role of these systems in addressing privacy concerns and the perception of risk. These concerns are examined from multiple angles, encompassing the viewpoints of private citizens (Arfi et al, 2021;Ben Arfi et al, 2021;Baudier et al, 2020a;Khan et al, 2022;Singh, 2022;Talukder et al, 2020) and public organizations, such as hospitals (Engin and G€ urses, 2019;Trkman et al, 2023). In the context of public organizations, with a specific focus on hospitals, the research investigates challenges related to the adoption of ATI, particularly considering the resistance to change among clinicians.…”
Section: Topic Modelingmentioning
confidence: 99%